New fossils of Australopithecus anamensis from Kanapoi, West Turkana, Kenya (2012–2015). Issue 140 (March 2020) - Ward, C.V.; Plavcan, J.M.; Manthi, F.K.
Abstract: Kanapoi, Kenya, has yielded the earliest evidence of the genus Australopithecus, Australopithecus anamensis . Renewed fieldwork from 2012 through 2015 yielded 18 new fossils attributable to this species. The new specimens include the second maxillary fragment known from a Kanapoi hominin and the first from a relatively young adult. The new maxilla has the distinctive rounded nasal aperture margin characteristic of A. anamensis . A second partial proximal tibia from the site is the first postcranial element from a small A. anamensis individual. A new partial mandible and complete mandibular dentition display distinctive Kanapoi hominin morphology, but the mandible displays a larger trigonid on its fourth premolar than any known so far. Two new complete sets of mandibular incisors are also notably large, especially the lateral ones, a distinctive feature of A. anamensis compared with Australopithecus afarensis . The new fossils also highlight the distinctive morphology of Kanapoi A. anamensis compared to later hominins.